Optimalisasi Konsumsi Fuel gas pada Boiler dengan Implementasi Sistem Kontrol Oxygen Excess Auto Cascade - Hidayat, Muhammad Taufik; Irawan, Bambang (Prosiding Seminar Nasional Teknoka, 2025)
Boilers accounted for 99.8% of total energy consumption at Badak LNG refinery. Of this usage, 15.1% was lost through blowdown, flue gas, and other boiler inefficiencies. The combustion control system was redesigned using a cascade configuration between the excess-oxygen loop (AIC-1) and the air-flow control loop (FIC-1). Each loop was modeled to obtain transfer functions that were then used to simulate responses to possible input disturbances. The simulation results yielded PID parameters that guided on-site loop tuning. In addition, layered logic protection and new alarms were integrated into the control system. As a result, system reliability was validated under external extremes, including abrupt boiler load increases and decreases. The optimization reduced the fuel-to-steam ratio by 0.6 Nm³/ton with the average boiler load over the past year of 207.6 ton/h, this corresponded to a 0.72% reduction in fuel-gas consumption.